Quantitative profiling of the endonuclear glycerophospholipidome of murine embryonic fibroblasts[S] - Tribble, Emily K.; Ivanova, Pavlina T.; Grabon, Aby; Alb, James G.; Faenza, Irene; Cocco, Lucio; Brown, H. Alex; Bankaitis, Vytas A. (Journal of lipid research, 2016)
A reliable method for purifying envelope-stripped nuclei from immortalized murine embryonic fibroblasts (iMEFs) was established. Quantitative profiling of the glycerophospholipids (GPLs) in envelope-free iMEF nuclei yields several conclusions. First, we find the endonuclear glycerophospholipidome differs from that of bulk membranes, and phosphatidylcholine (PtdCho) and phosphatidylethanolamine species are the most abundant endonuclear GPLs by mass. By contrast, phosphatidylinositol (PtdIns) represents a minor species. We also find only a slight enrichment of saturated versus unsaturated GPL species in iMEF endonuclear fractions. Moreover, much lower values for GPL mass were measured in the iMEF nuclear matrix than those reported for envelope-stripped IMF-32 nuclei. The collective results indicate that the nuclear matrix in these cells is a GPL-poor environment where GPL occupies only approximately 0.1% of the total nuclear matrix volume. This value suggests GPL accommodation in this compartment can be satisfied by binding to resident proteins. Finally, we find no significant role for the PtdIns/PtdCho-transfer protein, PITPα, in shuttling PtdIns into the iMEF nuclear matrix.